Optimización de iluminación de parques conforme a la Norma RTE INEN 069 basado en restricciones fotométricas - Mora Freire, Juan Francisco (2018)
With the creation of electricity and of his industrial application in the lighting of public and private sectors, the presence of light in a night environment is an element of great importance for the whole of Ecuador, which is governed by the Ecuadorian Standardization Service INEN. The main objective of this research is to optimize park lighting in accordance with the RTE INEN 069 standard based on photometric restrictions. In order to optimize the lighting, different criteria from different areas will be taken into account, in addition to the regulation of some spotlight manufacturers such as Phillips. On the other hand, lighting calculation programs are developed using the product database to ensure product selection o for urban projects. The result of the optimization is based on the calculations made by Calculux, which makes the recognition to establish a public lighting through an illuminance matrix and a simulation is made with GAMS that shows certain parameters that are related to the maximum height of the lighting assembly shows an optimization of the lighting of the roads of any park, thus complying with INEN standards, on which the average illuminance parameters are governed in Ecuador.